Konsep Optimisme pada Karakter Arrietty dalam Film Animasi Jepang “The Secret World of Arrietty (2011)” - Mu’alim Nur Ahsan; Syihabuddin Syihabuddin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study discusses how an animated character presents a concept of optimism that usually exists in humans. This research is descriptive qualitative research, in which the researcher examines the attitude of Arrietty's character which is in accordance with the concept of optimism. The data source for this research comes from an animated film made by Studio Ghibli entitled "The Secret World of Arrietty". The technique used for data collection in this study is the note-taking technique. Then for data processing it is grouped based on the dimensions of optimism proposed by Seligman. And the result is that Arrietty has all three dimensions of optimism but leans more towards the dimension of permanence.